Effect of parametric design in the performance optimization of vertical axis wind turbine: a review - Muhamad Fadhli Ramlee,; Ahmad Fazlizana,; Noorliyana Ramlee, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Wind energy is one of the renewable energy resources that is gaining attention from industry players and researchers. In the last few years, there is an increasing interest in small-scale wind turbines as a power generator in built environments as the urgency to reduce carbon footprint in urban areas increases as well as reducing adverse effects of fossil fuels on human health and the environment. Generally, wind turbines can be categorized into two categories which are horizontal axis wind turbines (HAWTs) and vertical axis wind turbines (VAWTs). VAWTs have good potentials to be developed considering their suitability to be used in complex wind conditions associated with built environments. However, the number of research, publications, as well as basic understanding of flow phenomena associated to the performance of VAWTs such as dynamic stall, flow separation, flow curvature effect and blade-wake interaction are scarce. These flow phenomena are attributed by operational and geometrical parameters that significantly affect the overall performance of VAWTs that includes turbine power generation and aerodynamic characteristics. This paper provides a review and discussion of the effects of various design parameters such as blade profile, blade pitch angle and turbine solidity on the performance of VAWTs and serves as a basic guideline to the designer in designing an ideal VAWT